Hysteretic behavior of the vortex lattice at the onset of the second peak for the HgBa2CuO4+delta superconductor - Stamopoulos, D.; Pissas, M. (PHYSICAL REVIEW B, 2002)
By means of local Hall probe ac and dc permeability measurements, we investigate the phase diagram of vortex matter for the HgBa2CuO4+delta superconductor in the regime near critical temperature. The second peak line H-sp, in contrast to what is usually assumed, does not terminate at the critical temperature. Our local ac permeability measurements reveal a pronounced hysteretic behavior and thermomagnetic history effects near the onset of the second peak, giving evidence of a phase transition of vortex matter from an ordered qausilattice state to a disordered glass.